The post-immersive manifesto. Issue 2 (3rd May 2020) - Lopes Ramos, Jorge; Dunne-Howrie, Joseph; Maravala, Persis Jadé; Simon, Bart
ABSTRACT: Over the past decade, 'immersive' has arguably been one of the most overused terms to describe theatre productions that aim to involve audiences in unconventional ways. With the mainstream success of specific 'immersive' productions, this trend goes beyond the theatre and arts industry. From games distributors to Westfield shopping centres, just about every organisation seems to be discussing how 'immersive' events can give their product an edgier public profile or increase sales. The need for a post-immersive manifesto comes from an assumption that the use of the term immersive is not helpful. And, in many ways, the use of the word 'immersive' to describe theatre productions can often be detrimental to the contract of expectations set up with audience members, guests, players, participants. This experimental manifesto is the result of five years of partnership between Technoculture, Arts & Games (Concordia University, Montréal) and ZU-UK (G.A.S. Station and MA in Contemporary Performance at University of Greenwich, London).